Inactivation of Inulinase and Marination of High-Quality Jerusalem Artichoke (Helianthus tuberosus L.) Pickles With Screened Dominant Strains - Zhang, Li; Liu, Wei; Ji, Jiahong; Deng, Lina; Feng, Qian; Shi, Wujian; Gao, Jian (Frontiers in Bioengineering and Biotechnology, 2021)
Freshly harvested Jerusalem artichoke tubers contain inulinase, which needs to be inactivated. Otherwise, inulin from Jerusalem artichokes is easily hydrolyzed by inulinase into fructose, which can be lost or consumed by bacteria during the marination process. The traditional pickling process lasts for six months, and a large amount of salt (18%–20%) is added during the pickling process. This production process is uneconomical and increases nitrite intake, and the miscellaneous bacteria that are produced during the pickling process affect product taste. In this study, reasonable enzyme inactivation methods, including NaCl, NaHCO3, and ultrasound, were evaluated. NaHCO3 showed the strongest enzyme inactivation; however, the quality and flavor of the obtained Jerusalem artichoke pickles were not ideal. The sensory flavor of Jerusalem artichoke pickles inactivated by NaCl was better, and enzyme inactivation was not obvious after ultrasound treatment, but ultrasound combined with NaCl resulted in enzyme inactivation. The inulinase activity of Jerusalem artichokes was reduced to 2.50 U/mL, and the inulin content was maintained at 61.22%, when the ultrasonic and NaCl combination treatment was applied. The strain LS3, identified as Enterococcus faecalis, and YS5, identified as salt-tolerant yeast Meyerozyma guilliermondii, were the dominant microorganisms isolated from the pickle juice. Jerusalem artichokes with inactivated inulinase were pickled with microbial powder, separated, purified, and dried to remove the natural Jerusalem artichoke sauce. This workflow shortened the fermentation cycle and improved product quality.